Al-Khazini in on the development of hydrostatic balance and its functionality - Danzomo, Bashir Ahmed; Shuriye, Abdi Omar (IIUM Press, 2011)
The significance of this chapter is to review the main contributions of al-Khazini in physics and scientific instruments. The methodology adopted in this chapter includes review of available and reliable literatures and data collected from library and internet sources. The main focus of the chapter is to present the work done by previous Muslim scientists on hydrostatics in the determinations of specific gravies of liquid, precious stones, metals and the hydrostatic balance designed and constructed by al-Khazini. Studies have shown that AI-Biruni and AI-Khazini performed the first scientific experimentations in areas of statics and dynamics; this is particularly for determination of specific weights, such as those based on the "theory of balances and weighing". The strict definition for a specific weight is given by AI-Khazini in "The Book of the Balance of Wisdom" and the reminder of the book is devoted to the description of various balances, beginning with balance attributed to Archimedes, proceeding through balances developed by Muslim scholars and concluding with an exhaustive description of the balance which al-Khazini calls "The Balance of Wisdom